PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN APLIKASI ARTICULATE STORYLINE 3 PADA PEMBELAJARAN IPAS UNTUK KELAS V SEKOLAH DASAR - Aulia Khairatunnisa; Yanti Fitria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by the low use of technology-based learning media in elementary schools.This research aims to develop interactive multimedia assisted by the Articulate Storyline 3 application in science and science learning about the digestive system in class V elementary school. The problems that occurred were obtained from the results of observations and interviews at several schools, namely SDN 04 Silaut, SDN 02 Silaut, SDN 06 Silaut, and SDN 11 Silaut. The results prove that teachers and students still rarely use technological learning media in the learning process, so that students experience a decrease in enthusiasm for learning and active learning while the learning process is in progress. This type of research uses a type of development research, namely Research and Development or usually abbreviated as (R&D). The media development uses the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The data collected in this research is validity, practicality and effectiveness data.The learning media that has been developed will be tested for validity by experts in the field, namely material experts, language experts and media experts by providing a validity questionnaire. The validity results show a percentage of 97% (very valid) for material experts, 94% (very valid) for linguists and 85% (very valid) for media experts. The practicality results prove that it is 92.28% (very practical) on the teacher practicality test and 96.45% (very practical) on the student practicality test.The effectiveness results prove that 82% (very effective) on student learning outcomes when using learning media. So it is concluded that the development of interactive multimedia assisted by the Articulate Storyline 3 application in science and science learning on digestive system material for class V elementary school is suitable for use in the learning process.